Atom Structure Analysis Approach For Video Forgery Identification - et. al., Punam Sunil Raskar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this high-tech world, editing of the video is made possible effortlessly by using advanced video editors. Misuse of these editors leads to manipulating the videos for hiding the truth. Traditional methods are computationally complex and slow for detecting the authenticity and integrity of such videos. The paper presents a fast method to detect manipulative videos by exploiting the atom structure analysis of the suspicious video. File format and metadata are another wellspring of scientific proof; however less consideration by researchers and investigators paid to these elements. The proposed work focuses on video forgery identification (VFI) method for MPEG-4 videos by investigating detailed file format information. The proposed system gives fast and accurate results as the examination of complete video frames is not required by this method. Thus tradeoff between accuracy and speed is optimized by this method. Implementation of the proposed system is performed on forged video dataset. Manipulated videos are created by using six different video editors. Experimental results demonstrate that the proposed system works efficiently for rendering binary output for all video editing software selected for experimentation. As well as, the system also correctly classifies frame addition and removal type of forgery.